Pengaruh Karakter dan Kepribadian Terhadap Motivasi Berprestasi yang Dimediasi Komitmen Mengajar - Syu'aib Nawawi (PROGRESSA: Journal of Islamic Religious Instruction, 2020)
The objectives of this study were to: 1) Test and analyze the character of teaching commitment. 2) Testing and analyzing the influence of personality on teaching commitment. 3) Testing and analyzing the influence of character on achievement motivation. 4) Testing and analyzing the influence of personality on achievement motivation. 5) Testing and analyzing the effect of achievement motivation on teaching commitment. 6) Testing and analyzing the effect of character indirectly on achievement motivation through teaching commitment. 7) Testing and analyzing the indirect influence of personality on achievement motivation through teaching commitment. This research is a descriptive-exploratory study with an exploratory, descriptive and explanatory design. The sample in this study was 38 people. The population in this study were all employees of the Trawas District, Mojokerto Regency, as many as 33 people. The sampling method in this writing uses census technique. Data analysis used SPSS version 26 for validity test with factor analysis, reliability test with Cronbach alpha. Classic assumption test and multiple linear regression analysis, to verify and prove the research hypothesis. To prove the hypothesis the writer used path analysis with SPSS V. 26 facilities. The results of the discussion concluded: 1) character has a significant effect on teaching commitment; 2) personality has a significant effect on teaching commitment; 3) character has a significant effect on achievement motivation; 4) personality has a significant effect on achievement motivation; 5) commitment to teaching has no effect on achievement motivation; 6) character has an indirect effect on achievement motivation through teaching commitment; 7) personality has an indirect effect on achievement motivation through teaching commitment.